Course experiences, satisfaction and career intent of final year pre-registration Australian pharmacy students - Shen G; Fois R; Nissen L; Saini B (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Background: In Australia, the profession of pharmacy has undergone many changes to adapt to the needs of the community. In recent years, concerns have been raised with evidence emerging of workforce saturation in traditional pharmacy practice sectors. It is not known how current final year pharmacy students' perceive the different pharmacy career paths in this changing environment. Hence investigating students' current experiences with their pharmacy course, interaction with the profession and developing an understanding of their career intentions would be an important step, as these students would make up a large proportion of future pharmacy workforce Objective: The objective of this study was thus to investigate final year students' career perspectives and the reasons for choosing pharmacy, satisfaction with this choice of pharmacy as a tertiary course and a possible future career, factors affecting satisfaction and intention of future career paths. Methods: A quantitative cross sectional survey of final year students from 3 Australian universities followed by a qualitative semi-structured interview of a convenience sample of final year students from the University of Sydney. Results: 'Interest in health and medicine' was the most important reason for choosing pharmacy (n=238). The majority of students were 'somewhat satisfied' with the choice of pharmacy (35.7%) as a course and possible future career. Positive associations were found between satisfaction and reasons for joining pharmacy such as 'felt pharmacy is a good profession' (p=0.003) while negative associations included 'joined pharmacy as a gateway to medicine or dentistry' (p=0.001). Quantitate and qualitative results showed the most frequent perception of community pharmacy was 'changing' while hospital and pharmaceutical industry was described as 'competitive' and 'research' respectively. The highest career intention was community followed by hospital pharmacy. Conclusion: Complex factors including university experiences are involved in shaping students' satisfaction and perception of career. This may relate to challenges in the community pharmacy sector, job opportunities in hospital and limited understanding of the pharmaceutical industry. The results offer insight for the profession in terms of entry into various roles and also to pharmacy educators for their roles in shaping curricula and placement experiences that attract future graduates to defined career pathways in pharmacy.